Generating Shigella that internalize into glioblastoma cells - Shipley, Austin; Frampton, Gabriel; Davies, Bryan W.; Umlauf, Benjamin J. (Frontiers in Oncology, 2023)
The use of microorganisms as drug delivery systems to treat cancer has expanded recently, including FDA approval of certain viruses as oncolytics. Microorganisms have several unique benefits compared to traditional pharmacologic agents including dose independence, the ability to produce therapeutic proteins locally within the tumor, and simplicity of administration. However, current microbial delivery systems such as AAV9 and herpes virus have limited cassette sizes, minimal cancer cell selectivity, and low innate cytotoxicity. To address these issues, we sought to generate a strain of Shigella flexneri to selectively internalize into glioblastoma (GBM) brain tumor cells as an initial step to generating a bacterial-based drug delivery system. We generated S. flexneri to selectively internalize into GBM cells using iterative co-cultured assays. After 50 rounds of co-culture, the new strain infected 95 percent of GBM cells in 2 hours. GBM-infecting Shigella demonstrate a 124-fold preference for internalizing in nine different GBM cell lines compared to Normal Astrocytes (NA) controls. Additionally, we developed an in-cell western to identify GBM-infecting Shigella clones that preferentially internalize in patient samples without iterative co-culture. Finally, we demonstrate internalization into GBM cells is mediated via a factor modified by myristoylation. In conclusion, here we present an novel bacterial platform that preferentially internalizes in brain tumor cells. This system provides numerous potential benefits over current interventions and other microbial strategies for treating brain tumors.